2021
DOI: 10.3991/ijet.v16i18.24315
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Chatbots for Learning among University Students: Role of Perceived Convenience and Enhanced Performance

Abstract: With the advent of internet and exponentially growing smartphone market, chatbots are becoming popular and are being widely used for interactions in varied fields. This study investigated the usage of chatbots for educational/learning purpose by university students. Wide research has been done exploring usage of chatbots in service industry; still there is vacuum regarding usage of chatbots in education for effective learning. Using path analysis, the study demonstrates validation of two newly added constructs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…Al Shamsi et al (2022) found that perceived usefulness was strongly positively correlated with the behavioural intention to use AI voice assistants. Malik et al (2021) found student perceptions of chatbots (eg, perceived convenience, ease of use) positively affected their intentions to use the technology in their learning. Gado et al (2021) focused on the KAP model and suggested that students were able to learn about AI when they felt in control (autonomy) and capable of using AI (competence).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Al Shamsi et al (2022) found that perceived usefulness was strongly positively correlated with the behavioural intention to use AI voice assistants. Malik et al (2021) found student perceptions of chatbots (eg, perceived convenience, ease of use) positively affected their intentions to use the technology in their learning. Gado et al (2021) focused on the KAP model and suggested that students were able to learn about AI when they felt in control (autonomy) and capable of using AI (competence).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This finding can then be considered to have supported that integration of CALL and chatbot will improve students' outcomes (Shawar, 2017). In addition, students can use chatbots at universities to help them learn more effectively (Malik et al, 2021).…”
Section: Students' Grammar Achievementmentioning
confidence: 86%
“…IGS (Malik et al, 2021) The lack of tools causes low performance in students in a virtual environment with respect to a second language.…”
Section: Vla (Uceda Et Al 2021)mentioning
confidence: 99%